Hipersensibilidade dentinária e qualidade de vida relacionada à saúde bucal: adaptação e validação do DHEQ-15, e revisão sistemática sobre o impacto do tratamento - Dhelfeson Willya Douglas de Oliveira (2018)
Dentin hypersensitivity (DH) is characterized by acute, sharp and short pain, and it may compromises the oral health related quality of life. The present thesis had 2 researches proposals, with specific objectives: 1) to adapt and to validate the short version of the Dentine Hypersensitivity Experience Questionnaire (DHEQ-15) into Portuguese for use in Brazil; 2) to investigate in the literature, using a systematic review, if the DH treatment is able to improve the quality of life of affected individuals. For cross-cultural adaptation, it was conducted a study with 5 steps according to preset criteria: translation of the original questionnaire into two Portuguese versions; synthesis of Portuguese versions; back-translation of the synthesized version into English; pre-test in a focus group; psychometric properties test of the translated instrument. An expert panel was set in order to monitor all process and to evaluate the reports from each step. The questionnaire was applied twice in 100 participants, with an interval of 7 to 10 days, in the last step. The DH was stimulated by air blast, and the level of sensitivity was assessed by Schiffs scale. The data were subjected to tests of internal consistency and validity, and they were analyzed by SPSS statistical software. The sample was composed of 69 men and 131 women, with mean age of 30.4 years. The focus group suggested two changes in the translated instrument. The Brazilian version presented Cronbach's alpha of 0.945, intraclass correlation coefficient of 0.959. There was statistically significant correlation (p<0.001) between DHEQ-15 score and oral health self-assessment. It was concluded that the Brazilian version of the instrument has good internal consistency, reliability and validity. For systematic review, the following electronic databases were searched until may 2017: PubMed/MEDLINE, Scopus, Web of Science, Cochrane Library, EMBASE, LILACS and Scielo, search strategies were adapted to each database. It were included clinical trials that assessed quality of life before and after any type of DH treatment. Three researchers independently selected studies, extracted data and assessed the methodological quality of the articles. The primary outcomes investigated were: type of treatment, inclusion criteria, assessment of quality of life and DH, results for DH and quality of life. Meta-analysis was conducted by I2, and the quality of evidence was determined by the Grading of Recommendations Assessment, Development, and Evaluation. It were identified 1805 references, and only six clinical trials were included in this review. The studies were developed in Sweden, Brazil, United States and Canada. The studies showed high statistical (I2=0.8407) and methodological heterogeneity. The level of evidence of this review ranged from very low to moderate. It was concluded that there are significant reduction of DH and significant improvement of quality of life of patients after DH treatment.